Simultaneous removal of hydrogen sulfide and mercury from simulated syngas by iron-based sorbents - Wang, J.; Zhang, Y.; Han, Lina; Chang, L.; Bao, W. (Elsevier Ltd, 2013)
Two iron oxide based sorbents, TG-1 and TG-F, with high desulfurization efficiency, were selected for simultaneous removal of H2S and Hg from simulated syngas. Our evaluation tests were carried out using a fixed bed reactor at different temperatures and in ambient atmosphere. The different activities for the simultaneous removal of H2S and Hg between TG-1 and TG-F or TG-1-S (denoted as such after uptake of H2S) were compared. The results show that the two iron oxide based sorbents can capture Hg effectively from simulated syngas. The preferred temperature for Hg removal using the TG-F and TG-1 sorbents are 60–120 degrees Celcius and 100–140 degrees Celcius, respectively. The Hg absorption capacity of TG-1 is higher than that of TG-F under the same conditions. CO and H2 in the feed gas have negligible effect on the efficiency of Hg removal. H2S is favoured for the removal of Hg over iron-based sorbents and it was found that the influence of H2S concentration on the Hg capacity of the TG-1 and TG-F sorbents are different. It is found that the main active components of the two sorbents during the reaction are different. After several desulfurizationcycles, the TG-1-S sorbent has a high efficiency for Hg removal from the simulated syngas.